2021
DOI: 10.1002/iub.2536
|View full text |Cite
|
Sign up to set email alerts
|

One‐year mortality and consequences of COVID‐19 in cancer patients: A cohort study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 21 publications
5
34
0
1
Order By: Relevance
“…Despite the limited number of patients involved in our work, our data confirm the impairment in the viral clearance in patients affected by hematological neoplasms, and the importance of early viral clearance on clinical outcome and overall survival. Patients who did not develop seroconversion after COVID-19 vaccination had higher probability of achieving viral clearance by 14 days, an independent predictor of overall survival at one year for unvaccinated patients [ 2 , 50 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the limited number of patients involved in our work, our data confirm the impairment in the viral clearance in patients affected by hematological neoplasms, and the importance of early viral clearance on clinical outcome and overall survival. Patients who did not develop seroconversion after COVID-19 vaccination had higher probability of achieving viral clearance by 14 days, an independent predictor of overall survival at one year for unvaccinated patients [ 2 , 50 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, COVID-19 symptoms are moderate or totally absent, with about one week of incubation period. Around 15% of patients can progress to severe pneumonia and about 5% eventually progress to acute respiratory distress pneumonia, renal failure, septic shock, multiple organ failure and death [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 outlines the significant findings with regard to changes in outcomes of patients with solid and/or haematologic malignancies following COVID-19 infection. 3 , 5 , 7 , 21 , 22 , 29 , 57–108 …”
Section: Introductionmentioning
confidence: 99%
“…In studies that included solid cancer patients, those who got COVID-19 had a higher probability of death compared with patients without cancer. 7 , 57 , 60 Several risk factors for increased mortality have been identified, including advanced age, male sex, smoking history, metastatic cancer, the presence of lung or bone metastases, higher C-reactive protein levels, the number of comorbidities and poor performance status. 7 , 21 Some studies found the age cut-off for worse prognosis to be 65 y, 96 while others found it to be 75 y.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation